Field performance of switchgrass plants engineered for reduced recalcitrance - Eudes, Aymerick; Lin, Chien-Yuan; De Ben, Christopher; Ortega, Jasmine; Lee, Mi Yeon; Chen, Yi-Chun; Li, Guotian; Putnam, Daniel H.; Mortimer, Jenny C.; Ronald, Pamela C.; Scown, Corinne D.; Scheller, Henrik V. (Frontiers in Plant Science, 2023)
Switchgrass (Panicum virgatum L.) is a promising perennial bioenergy crop that achieves high yields with relatively low nutrient and energy inputs. Modification of cell wall composition for reduced recalcitrance can lower the costs of deconstructing biomass to fermentable sugars and other intermediates. We have engineered overexpression of OsAT10, encoding a rice BAHD acyltransferase and QsuB, encoding dehydroshikimate dehydratase from Corynebacterium glutamicum, to enhance saccharification efficiency in switchgrass. These engineering strategies demonstrated low lignin content, low ferulic acid esters, and increased saccharification yield during greenhouse studies in switchgrass and other plant species. In this work, transgenic switchgrass plants overexpressing OsAT10 and QsuB were tested in the field in Davis, California, USA for three growing seasons. No significant differences in the content of lignin and cell wall-bound p-coumaric acid or ferulic acid were detected in transgenic OsAT10 lines compared with the untransformed Alamo control variety. However, the transgenic overexpressing QsuB lines had increased biomass yield and slightly increased biomass saccharification properties compared to the control plants.